Global geopolitical and economic prospects of the Corona pandemic (Damascus University Journal of arts and humanities sciences, 2021)
The effects of the Corona pandemic have been reflected on various aspects of life and at the local, regional and global levels. The future associated with the development of this pandemic appears unknown due to the ambiguity surrounding the origin, nature, cause, spread and continuity of the Corona virus, and many thinkers, international newspapers and study centers have tried to draw scenarios for the next stage in light of the outbreak of the Corona pandemic and After the decline after containment or expectation of a new wave in the fall, most of the scenarios that we examined in the study agreed on key points that the global economy is in a real dilemma, both in terms of the sharp decline in growth or in terms of the volume of trade exchanges, including the acute crisis of the oil sector in addition to The orientation of acclimatization, internal recession, lack of supply, increased demand, high unemployment rates and depletion of savings, and who will lead the global economy? And the importance of the role of governments in dealing with the pandemic and assuming their responsibilities, and the importance of the role of digital globalization, which will increase and be the driving nerve commercially and healthily, and a problem has also emerged for who will be the driver of the driving Here? China or the United States of America absolutely and then Russia, and the scenarios agreed on the problem of the continuity of neoliberalism and democracy in its current forms, and some scenarios have gone out that this global malaise will pass with minimal damage and its impact, especially economic ones, will be limited to2020and in the worst case for the first quarter of the year 2021, and if A scenario for punishing China has been passed, as this will lead to a war of existence for China. The scenarios indicated that the areas of tension and conflict will not make the pandemic less tense regions even if they cause a temporary cessation of this tension.
Keywords: Global geopolitical and economic prospects of the Corona pandemic